Film capacitors and resin films

JP7632690B2Active Publication Date: 2025-02-19MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023566160
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-07
Filing Date
2022-10-31
Publication Date
2025-02-19
Estimated Expiration
2042-10-31

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、高温下での絶縁破壊強度の高い樹脂フィルムを誘電体フィルムとして備えるフィルムコンデンサを提供することができる。さらに、本発明によれば、高温下での絶縁破壊強度の高い樹脂フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632690000003
    Figure 0007632690000003
  • Figure 0007632690000004
    Figure 0007632690000004
  • Figure 0007632690000005
    Figure 0007632690000005
Patent Text Reader

Abstract

A film capacitor 1 is provided with a dielectric film (e.g., a first dielectric film 11), and a metal layer (e.g., first metal layer 21) provided on at least one surface of the dielectric film. The dielectric film is a resin film formed of a cured object of: a first organic material having multiple hydroxyl groups in the molecule thereof; and a second organic material having multiple isocyanate groups in the molecule thereof. In a Fourier transform infrared spectroscopy (FT-IR) spectrum of the resin film, the intensity ratio of a peak within 1680<sp / >-1770 cm-1 derived from a carbonyl group in a urethane bond with respect to a peak within 1560<sp / >-1620 cm-1 derived from an aromatic ring is 0.50-0.94.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film capacitor and a resin film. [Background technology]

[0002] One type of capacitor is a film capacitor, which uses a flexible resin film as a dielectric and has a first counter electrode and a second counter electrode arranged opposite each other with the resin film sandwiched between them. Such a film capacitor is produced, for example, by winding or laminating a resin film on which a first counter electrode is formed and a resin film on which a second counter electrode is formed.

[0003] Patent Document 1 describes a film capacitor including a dielectric resin film and a metal layer provided on one surface of the dielectric resin film, the dielectric resin film having a glass transition temperature of 160° C. or higher and a density of 1.22 g / cm at 25° C. 3 More than 1.26g / cm 3 The following film capacitor is disclosed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 005822 Summary of the Invention [Problem to be solved by the invention]

[0005] In the film capacitor described in Patent Document 1, the density of the film is controlled to improve the glass transition temperature of the film, thereby increasing the dielectric breakdown strength at high temperatures. Patent Document 1 describes that the density of the film is increased by adjusting the solid content concentration in the resin solution, which is the coating liquid. However, increasing the solid content concentration increases the viscosity of the coating liquid, making it more difficult to increase the density as the thickness of the film decreases. As a result, it becomes difficult to increase the dielectric breakdown strength at high temperatures.

[0006] The present invention aims to provide a film capacitor including, as a dielectric film, a resin film having high dielectric breakdown strength at high temperatures. Another object of the present invention is to provide a resin film having high dielectric breakdown strength at high temperatures. [Means for solving the problem]

[0007] The film capacitor of the present invention includes a dielectric film and a metal layer provided on at least one surface of the dielectric film. The dielectric film is a resin film made of a cured product of a first organic material having a plurality of hydroxyl groups in its molecule and a second organic material having a plurality of isocyanate groups in its molecule. In the Fourier transform infrared spectroscopy (FT-IR) spectrum of the resin film, a peak at 1560 cm originating from an aromatic ring is detected. -1 More than 1620cm -1 The 1680 cm peak is due to the carbonyl group of the urethane bond. -1 over 1770cm -1 The intensity ratio of the following peaks is 0.50 or more and 0.94 or less.

[0008] The resin film of the present invention is made of a cured product of a first organic material having a plurality of hydroxyl groups in the molecule and a second organic material having a plurality of isocyanate groups in the molecule. -1 More than 1620cm -1 The 1680 cm peak is due to the carbonyl group of the urethane bond. -1over 1770cm -1 The intensity ratio of the following peaks is 0.50 or more and 0.94 or less. Effect of the Invention

[0009] According to the present invention, it is possible to provide a film capacitor including a resin film having high dielectric breakdown strength at high temperatures as a dielectric film. Furthermore, according to the present invention, it is possible to provide a resin film having high dielectric breakdown strength at high temperatures. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic example of a film capacitor of the present invention. [Diagram 2] FIG. 2 is an example of an FT-IR spectrum for calculating the intensity ratio of a peak derived from an isocyanate group to a peak derived from an aromatic ring. [Diagram 3] FIG. 3 is an example of an FT-IR spectrum for calculating the intensity ratio of the peak derived from a carbonyl group to the peak derived from an aromatic ring. [Figure 4] FIG. 4 shows an example of the results of measuring the storage modulus of a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The film capacitor and the resin film of the present invention will be described below. However, the present invention is not limited to the following configurations, and can be appropriately modified and applied within the scope of the present invention. The present invention also includes a combination of two or more of the individual preferable configurations of the present invention described below.

[0012] [Film capacitor] The film capacitor of the present invention comprises a dielectric film and a metal layer provided on at least one surface of the dielectric film.

[0013] The film capacitor of the present invention is, for example, columnar with an elliptical cross section, and external terminal electrodes formed by, for example, metal spraying (metallicon) are provided on both ends in the direction of the central axis.

[0014] Hereinafter, as an embodiment of the film capacitor of the present invention, a wound film capacitor in which a first dielectric film provided with a first metal layer and a second dielectric film provided with a second metal layer are wound in a laminated state will be described as an example. The film capacitor of the present invention may be a laminated film capacitor in which a first dielectric film provided with a first metal layer and a second dielectric film provided with a second metal layer are laminated. The film capacitor of the present invention may be a film capacitor in which a first dielectric film provided with a first metal layer and a second metal layer are wound or laminated, and a second dielectric film not provided with a metal layer is wound or laminated.

[0015] FIG. 1 is a cross-sectional view illustrating a schematic example of a film capacitor of the present invention.

[0016] The film capacitor 1 shown in Figure 1 is a wound-type film capacitor and comprises a first dielectric film 11 and a second dielectric film 12 in a wound state, a first metal layer (first opposing electrode) 21 and a second metal layer (second opposing electrode) 22 facing each other across the first dielectric film 11 or the second dielectric film 12, as well as a first external terminal electrode 31 electrically connected to the first metal layer 21 and a second external terminal electrode 32 electrically connected to the second metal layer 22.

[0017] The first metal layer 21 is provided on one surface of the first dielectric film 11, and the second metal layer 22 is provided on one surface of the second dielectric film 12. The first dielectric film 11 provided with the first metal layer 21 and the second dielectric film 12 provided with the second metal layer 22 are wound in a laminated state to form the film capacitor 1. The second dielectric film 12 may have a different configuration from the first dielectric film 11, but preferably has the same configuration as the first dielectric film 11.

[0018] The first metal layer 21 is formed on one surface of the first dielectric film 11 so as to reach one side edge but not to reach the other side edge. On the other hand, the second metal layer 22 is formed on one surface of the second dielectric film 12 so as to not reach one side edge but to reach the other side edge. The first metal layer 21 and the second metal layer 22 are composed of, for example, an aluminum layer.

[0019] 1, the first dielectric film 11 and the second dielectric film 12 are laminated with a shift relative to each other in the width direction so that an end of the first metal layer 21 that reaches the side edge of the first dielectric film 11 and an end of the second metal layer 22 that reaches the side edge of the second dielectric film 12 are both exposed from the laminated films. The first dielectric film 11 and the second dielectric film 12 are rolled in a laminated state, thereby maintaining the first metal layer 21 and the second metal layer 22 in a stacked state with their ends exposed.

[0020] In the film capacitor 1 shown in Figure 1, the second dielectric film 12 is wound so that it is on the outside of the first dielectric film 11, and the first metal layer 21 and the second metal layer 22 of each of the first dielectric film 11 and the second dielectric film 12 are wound so that they face inward.

[0021] The first external terminal electrode 31 and the second external terminal electrode 32 are formed by thermally spraying, for example, zinc on each end face of the capacitor body obtained as described above. The first external terminal electrode 31 contacts the exposed end of the first metal layer 21, and is thereby electrically connected to the first metal layer 21. On the other hand, the second external terminal electrode 32 contacts the exposed end of the second metal layer 22, and is thereby electrically connected to the second metal layer 22.

[0022] In the film capacitor of the present invention, the wound body of the dielectric film is preferably pressed into a flat shape such as an ellipse or an oval in cross section, and is more compact than when the cross section is a perfect circle. The film capacitor of the present invention may have a cylindrical winding shaft. The winding shaft is disposed on the central axis of the dielectric film in the wound state, and serves as the winding shaft when winding the dielectric film.

[0023] In the film capacitor of the present invention, examples of metals contained in the metal layer include aluminum (Al), titanium (Ti), zinc (Zn), magnesium (Mg), tin (Sn), and nickel (Ni).

[0024] In the film capacitor of the present invention, the thickness of the metal layer is not particularly limited, but is, for example, not less than 5 nm and not more than 40 nm. The thickness of the metal layer can be determined by observing a cross section of a dielectric film having a metal layer formed thereon, cut in the thickness direction, using an electron microscope such as a field emission scanning electron microscope (FE-SEM).

[0025] In the film capacitor of the present invention, it is preferable that a fuse portion is provided in the metal layer.

[0026] The fuse portion refers to a portion that connects the electrode portions of a metal layer that is a counter electrode and is divided into a plurality of parts. The pattern of the metal layer having the fuse portion is not particularly limited, and for example, the electrode patterns disclosed in JP-A-2004-363431 and JP-A-5-251266 can be used.

[0027] In the film capacitor of the present invention, the resin film of the present invention is used as the dielectric film. For example, in the film capacitor 1 shown in Fig. 1, both the first dielectric film 11 and the second dielectric film 12 may be the resin film of the present invention, or only one of them may be the resin film of the present invention.

[0028] [Resin film] The resin film of the present invention is made of a cured product of a first organic material having multiple hydroxyl groups in the molecule and a second organic material having multiple isocyanate groups in the molecule. Specifically, the resin film of the present invention is made of a cured product obtained by reacting the hydroxyl groups (OH groups) of the first organic material with the isocyanate groups (NCO groups) of the second organic material.

[0029] In the resin film of the present invention, when a cured product is obtained by the above reaction, the uncured part of the starting material may remain in the film. For example, the resin film of the present invention may contain at least one of a hydroxyl group and an isocyanate group. In this case, the resin film of the present invention may contain either one of a hydroxyl group and an isocyanate group, or may contain both a hydroxyl group and an isocyanate group. The presence of hydroxyl groups and / or isocyanate groups can be confirmed using a Fourier transform infrared spectrophotometer (FT-IR).

[0030] In the resin film of the present invention, the 1560 cm spectrum derived from an aromatic ring is -1 More than 1620cm -1 The 1680 cm peak is due to the carbonyl group of the urethane bond. -1 over 1770cm-1 It is characterized in that the intensity ratio of the following peaks is 0.50 or more and 0.94 or less.

[0031] In the resin film of the present invention, the dielectric breakdown strength can be increased by increasing the intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring.

[0032] The peak derived from the carbonyl group is due to the urethane bond formed by the reaction between the hydroxyl group of the first organic material and the isocyanate group of the second organic material. Therefore, it can be said that the higher the intensity of the peak derived from the carbonyl group, the higher the crosslink density. As the crosslink density increases, a denser mesh structure is formed and the interactions between molecules increase. Because the molecules are bound by the interactions, a large amount of energy (heat) is required to release the binding caused by the interactions. In other words, it is believed that the greater the interactions between molecules, the higher the glass transition temperature.

[0033] From the above, it is considered that the higher the intensity ratio of the peak derived from the carbonyl group of the urethane bond to the peak derived from the aromatic ring, the higher the glass transition temperature of the resin film.In addition, it is considered that the stability of the resin film in a high temperature range is improved by improving the glass transition temperature of the resin film, and the dielectric breakdown strength at high temperatures is improved.Alternatively, it is considered that the higher the crosslink density, the shorter the intermolecular distance and the suppression of the movement of carrier ions, and the dielectric breakdown strength is improved.

[0034] In the present invention, the intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring can be increased by proceeding with the reaction between the first organic material and the second organic material in a solution containing the first organic material and the second organic material for producing a resin film. The isocyanate, which is the second organic material, reacts with moisture in the air or the coating substrate to change into an amine compound via carbamic acid. Since the changed isocyanate cannot react with the hydroxyl group of the first organic material, the crosslink density decreases, and the glass transition temperature and dielectric breakdown strength of the resin film decrease.

[0035] By allowing the reaction between the first and second organic materials to proceed partially in the solution, molecular movement is restricted, increasing the reaction activation energy and suppressing deactivation by water. As a result, the formation of urethane bonds is not inhibited, and it is believed that the glass transition temperature and dielectric breakdown strength of the resin film are increased.

[0036] As described above, the glass transition temperature of the resin film can be increased by increasing the intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring. In the resin film of the present invention, the glass transition temperature is preferably 174.3°C or more and 192.1°C or less. This allows the resin film to have high heat resistance.

[0037] The glass transition temperature of the resin film can be calculated by measuring the storage modulus using a dynamic viscoelasticity measuring apparatus (DMA).

[0038] The first organic material is a polyol having a plurality of hydroxyl groups in the molecule. Two or more kinds of organic materials may be used in combination as the first organic material.

[0039] The first organic material preferably has an epoxy group, and in particular, the first organic material is preferably a phenoxy resin, and more preferably a high molecular weight bisphenol A type epoxy resin having an epoxy group at its terminal.

[0040] The second organic material is a polyisocyanate having multiple isocyanate groups in its molecule, and functions as a curing agent that hardens the film by reacting with the hydroxyl groups of the first organic material to form a crosslinked structure.

[0041] Examples of the second organic material include aromatic polyisocyanates such as diphenylmethane diisocyanate (MDI) and tolylene diisocyanate (also called toluene diisocyanate, TDI). Modified products of these polyisocyanates, for example, modified products having carbodiimide or urethane, may be used. As the MDI, a typical polymeric MDI may be used. Also, the MDI may be a monomeric MDI or a mixture type. As the TDI, a typical polymeric TDI may be used. Also, the TDI may be a monomeric TDI or a mixture type. As the second organic material, two or more organic materials may be used in combination.

[0042] The resin film of the present invention may also contain additives for adding other functions. For example, smoothness can be imparted by adding a leveling agent. The additive is preferably a material having a functional group that reacts with a hydroxyl group and / or an isocyanate group and that forms part of the crosslinked structure of the cured product. Examples of such materials include resins having at least one functional group selected from the group consisting of an epoxy group, a silanol group, and a carboxyl group.

[0043] The thickness of the resin film of the present invention is not particularly limited, but if the film is too thin, it is likely to become brittle. Therefore, the thickness of the resin film of the present invention is preferably 1 μm or more, more preferably 3 μm or more. On the other hand, if the film is too thick, defects such as cracks are likely to occur during film formation. Therefore, the thickness of the resin film of the present invention is preferably 10 μm or less, more preferably 5 μm or less.

[0044] The thickness of the film means the thickness of the film alone, not including the thickness of the metal layer. The thickness of the film can be measured using an optical film thickness meter.

[0045] [Manufacturing method of resin film] The resin film of the present invention is preferably obtained by forming a resin solution containing the first organic material and the second organic material into a film, and then curing it by heat treatment.

[0046] The resin solution is prepared, for example, by dissolving the first and second organic materials in a solvent, mixing them, and adding additives as necessary. Note that the solvent contained in the resin solution may remain as a residue in the cured film.

[0047] As described above, by partially progressing the reaction between the first organic material and the second organic material in the resin solution, the intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring can be increased.

[0048] The reaction between the first organic material and the second organic material in the resin solution is preferably carried out under heating and stirring in order to increase the reaction rate. The reaction rate may also be increased by using a catalyst or the like.

[0049] The method for reacting the first organic material with the second organic material in the resin solution is not particularly limited, and examples thereof include high-pressure homogenization, mechanical homogenization, and ultrasonic homogenization.

[0050] The weight ratio between the first organic material and the second organic material (first organic material / second organic material) is not particularly limited, but is, for example, not less than 10 / 90 and not more than 90 / 10.

[0051] As the solvent, it is preferable to use a mixed solvent containing a first solvent selected from ketones and a second solvent selected from cyclic ether compounds. Examples of ketones include methyl ethyl ketone and diethyl ketone. Examples of cyclic ether compounds include tetrahydrofuran and tetrahydropyran. The weight ratio of the first solvent to the second solvent (first solvent / second solvent) is not particularly limited, but is, for example, 15 / 85 or more and 85 / 15 or less.

[0052] [Manufacturing method of film capacitors] Next, an example of a method for producing the film capacitor of the present invention will be described. First, a metal layer is formed on one side of the dielectric film made of the resin film of the present invention to obtain a metallized film. Examples of the method for forming the metal layer include vapor deposition.

[0053] Two metallized films, each having a metal layer formed on one side of a dielectric film, are stacked with a predetermined distance offset in the width direction, and then rolled up to obtain a laminate. If necessary, the laminate may be sandwiched from a direction perpendicular to the width direction and pressed into an elliptical cylindrical shape.

[0054] Subsequently, external terminal electrodes are formed on the end faces of the laminate to obtain a film capacitor as shown in Fig. 1. Examples of a method for forming external terminal electrodes on the end faces of the laminate include thermal spraying. EXAMPLES

[0055] EXAMPLES Hereinafter, examples will be given that more specifically disclose the resin film of the present invention, but the present invention is not limited to these examples.

[0056] (Samples 1-8) As the first organic material, a phenoxy resin was prepared, and as the second organic material, 4,4-diphenylmethane diisocyanate (MDI) was prepared.

[0057] As the phenoxy resin, a phenoxy resin that is a high molecular weight bisphenol A type epoxy resin having an epoxy group at the terminal was used.

[0058] As the MDI, a typical polymeric MDI or monomeric MDI was used. As an expanded example, a mixture type MDI may also be used.

[0059] The first organic material and the second organic material were diluted and mixed with a mixed solvent containing methyl ethyl ketone (MEK) and tetrahydrofuran (THF) to obtain a first solution. The first organic material and the second organic material were reacted with each other while stirring the obtained first solution to obtain a second solution. The reaction rate between the first organic material and the second organic material was defined as the reaction rate of the second solution.

[0060] The reaction between the first organic material and the second organic material is preferably carried out under heating and stirring in order to increase the reaction rate. The reaction rate may also be increased by using a catalyst or the like.

[0061] The reaction method of the secondary solution is not particularly limited, and may be a method such as high-pressure homogenization, mechanical homogenization, or ultrasonic homogenization.

[0062] In this embodiment, a mixed solvent containing MEK and THF was used, but the type of solvent is not particularly limited.

[0063] The solvent used is preferably one which has been previously dehydrated by distillation or using a dehydrating agent.

[0064] In this example, the reaction rate of the second solution was controlled to be about 0 to 35% by adjusting the stirring time of the first solution to the time shown in Table 1.

[0065] The obtained secondary solution was cast on a PET film using a doctor blade coater, and the solvent was dried to obtain an uncured film having a thickness of 3 μm. The film was then heat-cured in a hot air oven set at 150° C. for 4 hours to obtain a film. Samples 1 to 8 were obtained in this manner.

[0066] (Samples 9-15) As the first organic material, a phenoxy resin was prepared, and as the second organic material, tolylene diisocyanate (TDI) was prepared.

[0067] As the phenoxy resin, a phenoxy resin that is a high molecular weight bisphenol A type epoxy resin having an epoxy group at the terminal was used.

[0068] As the TDI, a typical polymeric TDI or monomeric TDI was used. Alternatively, a mixture type TDI may be used as an expanded example.

[0069] The first organic material and the second organic material were diluted and mixed with a mixed solvent containing MEK and THF to obtain a first solution. The first organic material and the second organic material were reacted with each other while stirring the obtained first solution to obtain a second solution. The reaction rate of the first organic material and the second organic material was defined as the reaction rate of the second solution.

[0070] The reaction between the first organic material and the second organic material is preferably carried out under heating and stirring in order to increase the reaction rate. The reaction rate may also be increased by using a catalyst or the like.

[0071] The reaction method of the secondary solution is not particularly limited, and may be a method such as high-pressure homogenization, mechanical homogenization, or ultrasonic homogenization.

[0072] In this embodiment, a mixed solvent containing MEK and THF was used, but the type of solvent is not particularly limited.

[0073] The solvent used is preferably one which has been previously dehydrated by distillation or using a dehydrating agent.

[0074] In this example, the reaction rate of the secondary solution was controlled to be about 0 to 30% by adjusting the stirring time of the primary solution to the times shown in Table 2.

[0075] The obtained secondary solution was cast on a PET film using a doctor blade coater, and the solvent was dried to obtain an uncured film with a thickness of 3 μm. Next, this film was heat-cured in a hot air oven set at 150° C. for 4 hours to obtain a film. Samples 9 to 15 were obtained in this manner.

[0076] (Reaction rate of the second solution) The reaction rate of the secondary solution prepared under each condition was calculated using the following method.

[0077] The prepared secondary solution was applied to a film and dried at 70 °C for 1 minute. The FT-IR spectrum was measured on the dry surface of the obtained film, and the peak at 1590 cm originating from the aromatic ring was observed. -1 More than 1620cm -1 The 2200 cm peak due to the isocyanate group -1 More than 2350cm -1 The intensity ratio of the following peaks was calculated. The intensity ratio of the film prepared using unreacted secondary solution was used as the standard, and the reaction rate of each secondary solution was calculated from the reduction rate.

[0078] FIG. 2 is an example of an FT-IR spectrum for calculating the intensity ratio of the peak derived from the isocyanate group to the peak derived from the aromatic ring. In FIG. 2, the peak at 2200 cm derived from the isocyanate group -1 More than 2350cm -1 The following peak intensities are a n , 1590cm originating from aromatic ring -1 More than 1620cm -1 The following peak intensities are n As shown in Fig.

[0079] For the film prepared using the unreacted secondary solution, the 2200 cm -1 More than 2350cm -1 The following peak intensities are a0 and 1590 cm due to aromatic rings. -1 More than 1620cm -1 When the following peak intensity is designated as b0, the reaction rate of the secondary solution calculated by the following formula is shown in Tables 1 and 2. Reaction rate of the second solution (%) = {(A0-A n ) / A0}×100 A n =a n / b n A0=a0 / b0

[0080] (Intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring) The FT-IR spectrum was measured on the dry surface of the cured film, and the 1560 cm -1 More than 1620cm -1 The 1680 cm peak is due to the carbonyl group of the urethane bond. -1 over 1770cm -1 The intensity ratios of the following peaks were calculated.

[0081] FIG. 3 is an example of an FT-IR spectrum for calculating the intensity ratio of the peak derived from the carbonyl group to the peak derived from the aromatic ring. In FIG. 3, the peak at 1680 cm derived from the carbonyl group of the urethane bond is -1 over 1770cm -1 The following peak intensities are n , 1560cm originating from aromatic ring -1 More than 1620cm -1 The following peak intensities are n Denoted by c n / d n The peak intensity ratio (carbonyl group / aromatic ring) calculated from the ratio of the above is shown in Tables 1 and 2.

[0082] The FT-IR spectrum was measured by using a Fourier transform infrared spectrophotometer to measure the infrared absorption spectrum of the resin film by attenuated total reflection (ATR). -1 More than 4000cm -1 The measurements were performed using the JASCO FT / IR-4100ST. The ATR crystal was ZnSe and the incidence angle was 45°. The number of measurements was 16, and the resolution was 4cm. -1 It was decided.

[0083] (glass transition temperature) Each film was fixed to a width of 5 mm and a length of 6 mm, and the storage modulus of the film was measured using a dynamic viscoelasticity measuring device RSA3 (TA Instruments Japan Co., Ltd.) The temperature was raised from 40°C to 250°C at a rate of 20°C / min.

[0084] Figure 4 shows an example of the measurement results of the storage modulus of a film. The temperature at which the film changes from the glass region to the glass transition region was calculated as the glass transition temperature. Specifically, tangent lines were drawn to the graphs in the glass region and the glass transition region, and the intersection of the two lines was calculated as the glass transition temperature. The glass transition temperatures of each film are shown in Tables 1 and 2.

[0085] (Dielectric breakdown strength) After peeling each film from the PET film, aluminum vapor deposition electrodes (the electrode area of ​​the overlapping part is 30 cm) were attached to both sides. 2 ) was formed to prepare samples for evaluation. A voltage of 100 V / μm was applied to the prepared samples for 10 minutes, and then the voltage was increased in 25 V / μm intervals. Each voltage was held for 10 minutes, and the electric field strength was recorded when a trace of breakdown appeared on the film. Measurements were continued until breakdown was observed in a total of 16 locations. A Weibull plot was created based on the recorded results, and the value at which the failure rate was 50% was taken as the dielectric breakdown strength. The temperature around the film during the measurements was set to 125°C. The dielectric breakdown strength of each film is shown in Tables 1 and 2.

[0086] [Table 1]

[0087] [Table 2]

[0088] In Tables 1 and 2, samples marked with * are comparative examples outside the scope of the present invention.

[0089] In the case of Samples 8 and 15, the reaction between the first organic material and the second organic material in the solution proceeded too far, causing the solution to gel, and making it impossible to prepare a film.

[0090] From Tables 1 and 2, the 1560 cm -1 More than 1620cm -1 The 1680 cm peak is due to the carbonyl group of the urethane bond. -1 over 1770cm -1 It can be seen that the higher the intensity ratio of the following peaks, the higher the glass transition temperature and the higher the dielectric breakdown strength.

[0091] When the intensity ratio of the peak derived from the carbonyl group of the urethane bond to the peak derived from the aromatic ring is 0.41 or more and 0.47 or less, as in the case of samples 1, 2, 9 and 10, the glass transition temperature of the film is low, being 165.2°C or more and 170.4°C or less, and the dielectric breakdown strength is low, being 375 V / μm or more and 400 V / μm or less.

[0092] On the other hand, when the intensity ratio of the peak derived from the carbonyl group of the urethane bond to the peak derived from the aromatic ring is 0.50 or more and 0.94 or less as in the case of samples 3 to 7 and 11 to 14, the glass transition temperature of the film is very high at 174.3°C or more and 192.1°C or less, and the dielectric breakdown strength is high at 425 V / μm or more and 475 V / μm or less, and therefore the film shows excellent heat resistance and pressure resistance. [Explanation of symbols]

[0093] 1. Film capacitor 11 First dielectric film 12 Second dielectric film 21 First metal layer 22 Second Metal Layer 31 First external terminal electrode 32 Second external terminal electrode

Claims

1. A dielectric film; A film capacitor comprising: a metal layer provided on at least one surface of the dielectric film, the dielectric film is a resin film made of a cured product of a first organic material having a plurality of hydroxyl groups in its molecule and a second organic material having a plurality of isocyanate groups in its molecule; In the Fourier transform infrared spectroscopy (FT-IR) spectrum of the resin film, a 1560 cm 2 spectrum derived from an aromatic ring -1 1620cm or more -1 The following peaks are derived from the carbonyl group of the urethane bond at 1680 cm -1 1770cm or more -1 A film capacitor, wherein the intensity ratio of the following peaks is 0.50 or more and 0.94 or less:

2. The film capacitor according to claim 1 , wherein the resin film has a glass transition temperature of 174.3° C. or higher and 192.1° C. or lower.

3. A resin film made of a cured product of a first organic material having a plurality of hydroxyl groups in its molecule and a second organic material having a plurality of isocyanate groups in its molecule, In the Fourier transform infrared spectroscopy (FT-IR) spectrum of the resin film, a 1560 cm 2 spectrum derived from an aromatic ring -1 1620cm or more -1 The following peaks are derived from the carbonyl group of the urethane bond at 1680 cm -1 1770cm or more -1 A resin film having an intensity ratio of the following peaks of 0.50 or more and 0.94 or less.

4. The resin film according to claim 3 , wherein the resin film has a glass transition temperature of 174.3° C. or higher and 192.1° C. or lower.

Citation Information

Patent Citations

  • Film capacitor

    JP2015181199A

  • Film capacitor and dielectric resin film for film capacitor

    WO2020166392A1

  • Film capacitor and film for film capacitor

    WO2021005822A1

  • Film capacitor and film for film capacitor

    WO2021005823A1